Pengembangan Sistem Informasi Laboratorium Kesehatan (SILK) Di Politeknik Negeri Indramayu - Winani Winani; Bachtiar Efendi; A. Sumarudin (IKRA-ITH ABDIMAS, 2023)
Facilities and infrastructure standards are national education standards relating to minimum criteriaregarding study rooms, places to exercise, places of worship, libraries, laboratories, workshops, playgrounds,places for creation and recreation, as well as other learning resources, which are needed to support the learningprocess. including the use of information and communication technology (Government Regulation No. 19 of2005 concerning National Education Standards, 2005). One of these activities is the management of theNursing Laboratory, whose management must comply with standards to support student practice activities.Efforts are being made to support these activities by building a web-based application, namely the NursingLaboratory Information System (NLIS) which can be visited by accessing the Nursing Laboratory SystemInventory page via the URL: http://silk.polindra.ac.id/#. The program is expected to find errors and data thatcan be used for use and is very useful in Documented Recording of incoming and outgoing reports of goods,both medical devices and consumables, the formation of an information system related to recording andreporting on the inventory of tools and consumables, transferring technology, to provide convenience forstudents in using the laboratory, as well as improve the accessibility of data that is presented in a timely andaccurate manner for users.